59 Gosh arts – measuring patient experience of activity in outpatient waiting areas using the arts observational scale. (4th October 2017) - Hall, S; Moore, C
Abstract : Background: GOSH Arts is the arts programme at Great Ormond Street Hospital. Our wide-ranging work is designed to encourage creativity and improve the hospital environment of everyone. We deliver workshops, performances, exhibitions and art commissions that inspire creativity, create welcoming environments, and offer meaningful cultural opportunities for patients, families and staff. Project: Following a successful GOSHCC bid we were able to increase our provision in Outpatient waiting areas in 2015/2016. This was in response to the Outpatient Experience Survey conducted by Ipsos MORI in 2014 which indicated families disliked waiting and experienced stress in waiting rooms. Arts activities were identified as one way of mitigating these experiences and hopefully improving feedback. As well as our own on going evaluation mechanisms, we were interested to try and understand the impact of these arts interventions on patient and family experience. Evaluating arts interventions can be complex, particularly with limited resources, and where the focus is on actual delivery of a service. However we identified the recently developed Arts Observational Scale [1] as suitable for this context. This is a non–invasive validation scale that has been specifically developed to measure the impact of arts interventions in healthcare settings. This presentation will give an overview of the GOSH Arts programme, focusing on our delivery in outpatient waiting areas, and introduce the Arts Observational Scale and the results of its use at GOSH. Results: Headline findings: On average, 77%–83% of children who are in a waiting area when GOSH Arts Activities are taking place in waiting areas actively engage with the activities. The quality of the activities is rated 4.5/5 stars by parents and 4.4/5 by staff. 92% of parents believe the activities improve the family experience of being in hospital. 69% of parents report that the activities distract their child from being in hospital. Parents report that the activities make the waiting areas appear more safe, creative, caring and kind. 13% fewer children display disruptive behaviours in the waiting areas in the presence of activities compared to no activities.